Inisiasi Penerapan ISAK 335 pada Laporan Keuangan Yayasan: Studi Kasus pada Yayasan Hidayatullah Kabupaten Kepahiang - Nyimas Nispu Saharani; Abdullah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this research is to initiate the application of Interpretation of Financial Accounting Standards 335 (ISAK 335) in this financial statements of Hidayatullah Foundation of Kepahiang Regency. The hope is that the application of ISAK 335 can increase transparency, accountability, and public trust throught the preparation of financial reports that are in line with the accounting standards of non-profit organizations in Indonesia. This research uses a descriptive qualitative approach to data collection techniques through observation, interviews, and documentation. The results show that Hidayatullah Foundation previously only prepared cash in and out reports without a standard financial report format. However, with the application of ISAK 335, the foundation now has a more structured report, including a more structured Statement of Financial Position, Statement of Comprehensive Income, Statement of Changes in Net Assets, Statement of Cash Flows, and Notes to Financial Statements. It is hoped that this research can be a reference for other non-profit organizations in improving the quality of financial statements, so as to encourage organizational accountability and sustainability.